Synthetic anticonvulsants, antihypoxic agents, and inducers of the liver monooxygenase system; XII; The enzyme-inducing activity of N-aralkyl-N-acylureas; Pharmaceutical Chemistry Journal; Vol. 28, iss. 3 - Bakibaev A. A. Abdigali Abdimanapovich; Akhmedzhanov R. R. Rafik Raviljevich; Tignibidina L. G.; Novozheeva T. P.; Shtrykova V. V. Viktoriya Viktorovna; Filimonov V. D. Viktor Dmitrievich; Dobychina N. S.; Saratikov A. S. (1994, 1994)
Title screen